THE INFLUENCE OF THE LEVEL KNOWLEDGE TAXPAYERS ON COMPLIANCE WITH PAYING LAND AND BUILDING TAX IN TAMBAKMEKAR VILLAGE KEC. JALANCAGAK KAB. SUBANG - Tsara Afifah (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
Taxpayer compliance is one thing that is important and needs to be considered in the government's efforts to maximise state revenue from the tax sector. This study aims to determine the effect of the level of taxpayer knowledge on compliance with paying land and building tax in Tambakmekar Village, Jalancagak District, Subang Regency. State taxes will increase if the level of community compliance as a high taxpayer tax. Tax compliance is still fluctuating when viewed from the timeliness of payment. The purpose of this study was to examine the analysis of the effect of taxation knowledge in building compliance to pay taxes. This type of quantitative research with a sample of 34 taxpayers. The sampling technique used Accidental Sampling Data collection techniques using questionnaires and data analysis techniques with descriptive analysis and Simple Regression analysis. Descriptive analysis shows taxpayer compliance, quite good. The results showed that there was a significant effect of the influence of tax knowledge on compliance of land and building taxpayers in Tambakmekar Village, Jalancagak District, Subang Regency.